SOA governance in action : REST and WS-* architectures - Dirksen, Jos. (Shelter Island, NY : Manning, 2013)
Good run through how to implement distributed services and the solutions that help to govern SOA such as business activity monitoring at the implementation level.
&#x000A
Includes index.
oif 08/09/14
Loan
Keywords: Service-oriented architecture (Computer science); Representational State Transfer (Software architecture); Computer network architectures